Making Insulin and Staying Out of Autoimmune Trouble: The Beta-Cell Conundrum - Carré, Alexia; Mallone, Roberto (Frontiers in Immunology, 2021)
Autoimmune type 1 diabetes (T1D) results from the intricate crosstalk of various immune cell types. CD8+ T cells dominate the pro-inflammatory milieu of islet infiltration (insulitis), and are considered as key effectors of beta-cell destruction, through the recognition of MHC Class I-peptide complexes. The pathways generating MHC Class I-restricted antigens in beta cells are poorly documented. Given their specialized insulin secretory function, the associated granule processing and degradation pathways, basal endoplasmic reticulum stress and susceptibility to additional stressors, alternative antigen processing and presentation (APP) pathways are likely to play a significant role in the generation of the beta-cell immunopeptidome. As direct evidence is missing, we here intersect the specificities of beta-cell function and the literature about APP in other cellular models to generate some hypotheses on APPs relevant to beta cells. We further elaborate on the potential role of these pathways in T1D pathogenesis, based on the current knowledge of antigens presented by beta cells. A better understanding of these pathways may pinpoint novel mechanisms amenable to therapeutic targeting to modulate the immunogenicity of beta cells.